Implementasi Mobile Augmented Reality Pada Aplikasi Pemilihan Sarana Dan Prasarana Laboratorium Sekolah Menengah Atas - Dimas Setyo Utomo; Issa Arwani; Wibisono Sukmo Wardhono (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2017)
Augmented Reality (AR) is a technology with a lot of potentials. AR could bring a lot of advantages in many different fields such as entertainment, design or military. This technology also possibly used as a new design approach for interior design as virtual objects such as furniture displayed in a real-world environment on the screen. This study took up in an institution like public school specifically for school laboratory. This study will also add the use of Head Mounted Display (HMD) such as Google Cardboard for better user experience. The objects were designed and shown in 3D with a certain standard for public high school laboratory. Plus, the object's material can be changed through Google Cardboard's view.